HYPERTROPHIC CARDIOMYOPATHY WITH MIDVENTRICULAR OBSTRUCTION IN ASSOCIATION WITH OSTIUM SECUNDUM-TYPE ATRIAL SEPTAL DEFECT. Issue 3 (July 2005) - Aydın, Mustafa; Doğan, Sait Mesut; Gürsürer, Metin; Dursun, Tolga Onuk Aydın; Cam, Fatih
No abstract available